Formulation and characterization of zein/chitosan complex particles stabilized Pickering emulsion with the encapsulation and delivery of vitamin D3. (9th March 2021) - Shah, B R; Xu, W; Mráz, J
Abstract: BACKGROUND: Pickering emulsions (PEs) which are stabilized by solid particles instead of surfactants have recently attracted tremendous attentions due to their non‐toxic and long‐term stable nature. In the current study, we fabricated and characterized zein (ZN)/chitosan (CS) complex particles (ZNCSPs) stabilized PE for the encapsulation and delivery of vitamin D3 . RESULTS: The ZNCSPs were synthesized with different ratios, i.e. 1:1, 1:1.5 and 1:2 to investigate the optimum ratio. Transmission electron microscopy observations showed the spherical nature with smooth surface of the obtained particles in the case of ZNCS ratio 1:1.5 and 1:2. Furthermore, ζ‐potential values for the these particles were 32.53 ± 1.3 and 52.86 ± 0.68 mV respectively, indicating particles with (1:2) being more stable than 1:1.5. Thereafter, using these particles, the PEs were successfully formulated with different oil (medium chain triglyceride) fractions (330, 500 and 660 g kg −1 ). The emulsions were evaluated for stability during storage and against different environmental factors including pH, temperature and ionic strength on the creaming indices (CIs) of these emulsions. The results demonstrated that the PEs with oil fractions 330 and 500 g kg −1 exhibited significant stability during storage, particularly the ones with 500 g kg −1 oil fractions which were stable against all the tested parameters. Finally, the prepared PEs were evaluated as efficient delivery system by encapsulating and delivering vitamin D3 . In vitro drug release profile confirmed sustained and controlled release of the encapsulated vitamin D3 . CONCLUSION: Overall, our findings suggest that ZNCSPs can be promising stabilizers for stable PEs that can be used as potential delivery systems in food, cosmetic and pharmaceutical industries. © 2021 Society of Chemical Industry.